OPTIMALISASI FORMULA KANDUNGAN ZAT BAHAN PAKAN DOMBA DAN KAMBING DENGAN MULTIVARIATE LINEAR REGRESSION - Badruz Zamanil Charis; Usman Pagalay; Mokhamad Amin Hariyadi; Muhammad Farid Wadjdi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Animal feed is one of the most important things for sheep and goat farming. Without a good balance of feed ingredients, sheep and goats will not grow optimally, because the feed given to livestock does not match their needs. Therefore, we need an appropriate way to regulate the nutritional needs of feed required by sheep and goats. This study aims to meet the nutritional needs of sheep and goats from a variety of concentrate and forage feed ingredients. To meet the nutritional needs of feed ingredients, it is necessary to do research on optimization in the manufacture of ration feed formulas. If the nutritional needs have been met, the next goal is to predict the price of the ration economically in order to provide a profit. To solve this problem, an approach is needed to model the relationship between concentrate feed ingredients and forage feedstuff variables. Multivariate linear regression is a regression analysis method that involves more than one response variable.